2004
DOI: 10.1261/rna.7660804
|View full text |Cite
|
Sign up to set email alerts
|

Functional analysis of mRNA scavenger decapping enzymes

Abstract: Eukaryotic cells primarily utilize exoribonucleases and decapping enzymes to degrade their mRNA. Two major decapping enzymes have been identified. The hDcp2 protein catalyzes hydrolysis of the 5 cap linked to an RNA moiety, whereas the scavenger decapping enzyme, DcpS, functions on a cap structure lacking the RNA moiety. DcpS is a member of the histidine triad (HIT) family of hydrolases and catalyzes the cleavage of m 7 GpppN. HIT proteins are homodimeric and contain two conserved 100-amino-acid HIT fold domai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
119
1
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 76 publications
(126 citation statements)
references
References 37 publications
5
119
1
1
Order By: Relevance
“…The saturated amplitudes indicate that the DcpS-cap complex K d is Ͻ20 nM (Fig. 1E), consistent with the K d of 75 nM we previously reported (29).…”
Section: Hydrolysis Of Cap Structure By Dcps Is Rate-limiting At the supporting
confidence: 91%
“…The saturated amplitudes indicate that the DcpS-cap complex K d is Ͻ20 nM (Fig. 1E), consistent with the K d of 75 nM we previously reported (29).…”
Section: Hydrolysis Of Cap Structure By Dcps Is Rate-limiting At the supporting
confidence: 91%
“…Findings presented by Mike Kiledjian (Rutgers) provide an explanation for the observa-tion that intact mRNAs are not substrates for DcpS. Kiledjian showed that the affinity and subsequent activity of mammalian DcpS for 5Ј cap structures is sensitive to the length of the RNA in which the cap is attached Liu et al 2004). DcpS demonstrates 2500-fold greater activity on a capped dinucleotide versus a full-length capped mRNA substrate, and, moreover, the robust activity of DcpS on capped decay intermediates effectively competes for, and hydrolyzes, cap structure in the presence of the cap-binding protein, eIF4E.…”
Section: Mrna Stabilization By Cis-acting Elements: Parallels Betweenmentioning
confidence: 99%
“…DcpS utilizes an evolutionarily conserved Histidine Triad (HIT) motif (Liu et al 2002) to hydrolyze the triphosphate linkage of the cap structure and is the only known cap-binding protein that hydrolyzes its substrate (Liu et al 2002). Despite its purification from cytoplasmic extract (Liu et al 2002) and its well-characterized cytoplasmic decapping function (Liu et al 2002;van Dijk et al 2003;Cohen et al 2004), DcpS is predominantly if not exclusively a nuclear protein by immunocytochemistry (Salehi et al 2002;Cougot et al 2004;Liu et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Recent experiments reveal an auto-regulatory mechanism whereby DcpS positively feeds back onto the 59-39 directional mRNA degradation pathway (Liu and Kiledjian 2005). Despite these studies that emphasize cytoplasmic functions, the unexpected DcpS nuclear localization (Cougot et al 2004;Liu et al 2004) strongly indicates an unknown nucleus-associated function.…”
Section: Introductionmentioning
confidence: 99%